2020
DOI: 10.1016/j.visres.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

3D shape-from-shading relies on a light source prior that does not change with age

Abstract: The light-from-above prior enables observers to infer an object's three-dimensional shapefrom-shading information. Young, Western adults implicitly assume the light source is placed not only above, but also to the left of, the observer. Previous evidence reached conflicting conclusions regarding the development of the assumed light source direction. In the present study, we measured the light source prior cross-sectionally in children aged 5-11 years, using an explicit shape judgement task. The light-from-abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It is unclear whether this shift in the emergence of the general visual response is due to a differential activation of the center-surround receptive fields in the retina or the lateral geniculate nuclei (Meister and Berry, 1999), and/or whether it is due to contrast negation hindering general, low-level visual processing in the cortex (e.g. perception of brightness: Yang and Purves, 2004;Pickard-Jones et al, 2020;orientation;Girshick et al, 2011;apparent contrast: Bex and Makous, 2002;Haun and Peli, 2013). Hence, shading, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear whether this shift in the emergence of the general visual response is due to a differential activation of the center-surround receptive fields in the retina or the lateral geniculate nuclei (Meister and Berry, 1999), and/or whether it is due to contrast negation hindering general, low-level visual processing in the cortex (e.g. perception of brightness: Yang and Purves, 2004;Pickard-Jones et al, 2020;orientation;Girshick et al, 2011;apparent contrast: Bex and Makous, 2002;Haun and Peli, 2013). Hence, shading, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast negation induced a moderate shift in the onset of the general visual response toward higher contrast values, but did not affect the level of contrast required to elicit an optimal general visual response or its overall magnitude. It is unclear whether this shift in the emergence of the general visual response is because of a differential activation of the center-surround receptive fields in the retina or the lateral geniculate nuclei ( Meister and Berry, 1999 ), and/or whether it is because of contrast negation hindering general, low-level visual processing in the cortex (e.g., perception of brightness, Yang and Purves, 2004 ; Pickard-Jones et al, 2020 ; orientation, Girshick et al, 2011 ; apparent contrast, Bex and Makous, 2002 ; Haun and Peli, 2013 ). Hence, shading, i.e., the pattern of luminance across a surface, is informative of the structural properties of many things around us, not just faces.…”
Section: Discussionmentioning
confidence: 99%
“…Shading and border structure help an observer identify a three-dimensional object's shape but shape-fromshading percepts can produce false illusions of depth in two-dimensional objects [15,16,22]. Visual perception integrates sensory data with sensory biases acquired from prior experiences ("priors"), including the expectation that the shading of natural objects is caused by a single light source [15][16][17][18][19][20][21][22]. Shape-from-shading pseudo3D illusions have also been observed previously in scanning electron microscopy [58] and retinal differential interference contrast microscopy images.…”
Section: Pseudo3d Is Shape-from-shadingmentioning
confidence: 99%
“…It also facilitates identification of large-area chorioretinal irregularities not readily displayed in other en face retinal imaging modalities [11][12][13][14]. Shaded boundaries create the perception of elevation or depression in imaged structures [15][16][17][18][19][20][21][22], a characteristic of retroillumination but not standard reflectance SLO imaging. This perception is an illusion rather than an objective three-dimensional representation of chorioretinal anatomy as provided by optical coherence tomography (OCT).…”
Section: Introductionmentioning
confidence: 99%
“…This is also a conservative estimate. In a study by Pickard-Jones, D'Avossa, and Sapir (2020) using the honeycomb stimulus, all 58 children between the ages of 7 and 11 years showed a bias to lighting from above. In addition, using shaded bubbles, Sun and Perona (1998) found that 12 adults (evenly split for handedness) all had biases to lighting from above.…”
mentioning
confidence: 99%